2000
DOI: 10.1046/j.1365-2265.2000.00951.x
|View full text |Cite
|
Sign up to set email alerts
|

Hormone levels and tumour size response to quinagolide and cabergoline in patients with prolactin‐secreting and clinically non‐functioning pituitary adenomas: predictive value of pituitary scintigraphy with 123I‐methoxybenzamide

Abstract: An intense 123I-IBZM uptake in patients with non-functioning adenomas was predictive of a good response to a chronic treatment with quinagolide and cabergoline. This result suggests that a pituitary 123I-IBZM scintigraphy could be considered in selected patients with non-functioning adenomas before starting medical treatment with dopamine agonists.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
45
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(46 citation statements)
references
References 46 publications
1
45
0
Order By: Relevance
“…Therefore, bromocriptine therapy has not been advocated on a routine basis. Better, but still variable, results have been reported on the treatment with the nonergot DA agonist quinagolide and the specific DA agonist cabergoline (20,23,26,27,34,35,39). The heterogeneity of responses to treatment has been attributed to the different pattern and level of expression of dopamine receptor subtypes in the individual tumors, as well as to possible alterations in the receptor-related signal transduction pathway (10,27,38).…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Therefore, bromocriptine therapy has not been advocated on a routine basis. Better, but still variable, results have been reported on the treatment with the nonergot DA agonist quinagolide and the specific DA agonist cabergoline (20,23,26,27,34,35,39). The heterogeneity of responses to treatment has been attributed to the different pattern and level of expression of dopamine receptor subtypes in the individual tumors, as well as to possible alterations in the receptor-related signal transduction pathway (10,27,38).…”
Section: Discussionmentioning
confidence: 95%
“…We have previously demonstrated the superiority of 123 Iepidepride over 123 I-IBZM (31). In a series of ten patients with NFPA, the clinical usefulness of 123 I-IBZM scintigraphy for predicting tumor response to DA agonists could be demonstrated in two with high tumor uptake of the radioligand (34). Therefore, we studied the correlation between in vivo imaging of D2 receptors using 123 Iepidepride and the response of NFPA to long-term DA agonist therapy, as evaluated by magnetic resonance imaging (MRI).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therapeutic trials may be performed in cases of recurring adenomas or when surgery is contraindicated. In vivo scintigraphy using D2 agonists (25,26), or in vitro D2 receptor studies in recurring tumors may allow a better selectivity in the therapeutic choice.…”
Section: Discussionmentioning
confidence: 99%
“…3/day and 0.5 mg/day respectively, had been employed. Recent studies on patients with NFA treated with somatostatin analogues have shown a rapid improvement of the visual field in most cases (56,57).…”
Section: Non-functioning Pituitary Adenomasmentioning
confidence: 99%